Data structuring for 3D spatial objects - Abd. Khalid, Harith Fadzilah; Abdul Rahman, Alias (2007)
This paper describes one aspect of 3D GIS research, that is the data structuring for 3D objects and incorporate with geo-DBMS. Geo-database can manage large spatial data sets and able to provide access to multi users. Lately there are growing tendency towards the multifunctional use of space i.e. above and below the ground surface. Applications such as urban planning, telecommunication and 3D cadastre depend on 3D data. Thus, the need for managing the 3D spatial datasets especially for large area is inevitable. A discussion on how to establish these data structures for managing 3D spatial objects of large areas form major discussion of this paper. 3D primitives like points, lines, surfaces (or polygons) and solids are part of the primitives. The mapping of this structure in Oracle Spatial DBMS will be highlighted as well. Our presentation also will highlight the future outlook of the data structuring approach for managing large volume of 3D spatial objects and relates with current research development in 3D GIS.